1999
DOI: 10.2307/2649199
|View full text |Cite
|
Sign up to set email alerts
|

Faculty and Administrators' Attitudes toward Potential Conflicts of Interest, Commitment, and Equity in University-Industry Relationships

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ohio State University Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Higher Education.In the 1940s the federal government began aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 12 publications
(15 reference statements)
0
71
1
Order By: Relevance
“…For instance, combining research (i.e., the number of publications and the number of conference presentations/exhibitions) and funds (i.e., serving as a principal investigator on an externally funded project and total research funds) as a single "research" measure, Fairweather (2002) found that only 22% of university faculty were productive in both teaching and research, whereas about 50% of faculty in research universities were productive in either research or teaching. Campbell and Slaughter (1999) warned that disparities between entrepreneurial and non-entrepreneurial faculty will continue to widen, with entrepreneurial faculty engaging in university-industry activity and non-entrepreneurial faculty involved with traditional academic duties (i.e., teaching and attention to students). Entrepreneurial faculty are likely to increase in status and prestige, while the status of non-entrepreneurial faculty will diminish (Campbell and Slaughter, 1999).…”
Section: Entrepreneurial Activities and Teachingmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, combining research (i.e., the number of publications and the number of conference presentations/exhibitions) and funds (i.e., serving as a principal investigator on an externally funded project and total research funds) as a single "research" measure, Fairweather (2002) found that only 22% of university faculty were productive in both teaching and research, whereas about 50% of faculty in research universities were productive in either research or teaching. Campbell and Slaughter (1999) warned that disparities between entrepreneurial and non-entrepreneurial faculty will continue to widen, with entrepreneurial faculty engaging in university-industry activity and non-entrepreneurial faculty involved with traditional academic duties (i.e., teaching and attention to students). Entrepreneurial faculty are likely to increase in status and prestige, while the status of non-entrepreneurial faculty will diminish (Campbell and Slaughter, 1999).…”
Section: Entrepreneurial Activities and Teachingmentioning
confidence: 99%
“…Campbell and Slaughter (1999) warned that disparities between entrepreneurial and non-entrepreneurial faculty will continue to widen, with entrepreneurial faculty engaging in university-industry activity and non-entrepreneurial faculty involved with traditional academic duties (i.e., teaching and attention to students). Entrepreneurial faculty are likely to increase in status and prestige, while the status of non-entrepreneurial faculty will diminish (Campbell and Slaughter, 1999).…”
Section: Entrepreneurial Activities and Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bayh-Dole Act in 1980 was the first legislation that allowed universities to start spin-off businesses and to generate profits from patents (Campbell & Slaughter, 1999). As a result, university partnerships with the private sector have greatly increased through research grants, licensing patents, and in some cases, the formation of new firms-mainly at research universities and in the hard sciences.…”
Section: Introductionmentioning
confidence: 99%